Re-Construction of the Small Xanten-Wardt Dart Launcher - Michele Fratino; Luis Palmero Iglesias; Adriana Rossi (Engineering Proceedings)
Based on the dimensions of the small Xanten catapult, this study reconstructs a full-scale model to validate its manufacturing techniques and evaluate its effectiveness. The process underscores the role of experimental archaeology: the activity facilitates a dynamic sequence of queries, guides the interpretation of signs—not merely physical ones—refines the perception of the cognitive model, and relies on an interdisciplinary approach and strategy. The reconstruction fosters social engagement and scientific dialogue, supporting the adoption of new strategies for knowledge transmission and cultural valorization. The conclusions of this study contribute to the debate on the causes of damage inflicted by the Roman legions on the perimeter walls of Pompeii.